2014
DOI: 10.1111/lam.12346
|View full text |Cite
|
Sign up to set email alerts
|

Preservative activity of lavender hydrosols in moisturizing body gels

Abstract: The presented research proved antimicrobial activity of hydrosols obtained from fresh or dried Lavandula angustifolia herbs or flowers in moisturizing body gel. The study shows the usefulness of lavender hydrosols as a natural, ecologically friendly component of cosmetics with potential preservative activity in formulations. Hydrosols are commonly regarded as waste in the production of essential oils. The use of lavender hydrosols in the cosmetic industry as a replacement for water phase in cosmetics may not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…The opposite was reported on cosmetics formulated with vegetal extracts by Kunicka-Styczynska et al [42], who observed that the microbial population decreased within 14 days with no increase up to the 28th day. It is probable that increased concentration of natural preservatives could be beneficial either alone or in combination with synthetic agents.…”
Section: Sun Creamsmentioning
confidence: 73%
“…The opposite was reported on cosmetics formulated with vegetal extracts by Kunicka-Styczynska et al [42], who observed that the microbial population decreased within 14 days with no increase up to the 28th day. It is probable that increased concentration of natural preservatives could be beneficial either alone or in combination with synthetic agents.…”
Section: Sun Creamsmentioning
confidence: 73%
“…In the formulations are, hydrolates act as both small valuable biologically active components and Potentially preservative agents [23]. Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that volatile lavender oil has antioxidant, antimicrobial and antifungal properties [ 42 ]. The antioxidant and antimicrobial capacity of lavender volatile oil is offered by compounds such as the monoterpenoids, linalool, linalyl acetate, 1,8-cineole, β-ocimene, terpinen-4-ol, and camphor [ 43 , 44 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%